2011
DOI: 10.1242/jcs.080200
|View full text |Cite
|
Sign up to set email alerts
|

MLCK regulates Schwann cell cytoskeletal organization, differentiation and myelination

Abstract: SummarySignaling through cyclic AMP (cAMP) has been implicated in the regulation of Schwann cell (SC) proliferation and differentiation. In quiescent SCs, elevation of cAMP promotes the expression of proteins associated with myelination such as Krox-20 and P0, and downregulation of markers associated with the non-myelinating SC phenotype. We have previously shown that the motor protein myosin II is required for the establishment of normal SC-axon interactions, differentiation and myelination, however, the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 69 publications
3
24
0
Order By: Relevance
“…3e , Supplementary Data 5 ) were the pathways most represented. β1 integrin and RhoC were constituents of these three pathways ( Supplementary Data 5 ), suggesting a potentially important role for RhoC, given that β1 integrin and other small Rho GTPases and effectors (Rac1, Cdc42, Rock and Mlck) are required for axo-glial interactions 6 21 26 27 28 . Similarly, 9 out of the 10 most abundant pathways shared the heterotrimeric G proteins encoded by Gnb1 , Gnb2 , Gnb2L1 , Gnao1 and Gnai2 ( Supplementary Data 5 ), which expand the notion that G-protein signalling is a major contributor of radial sorting and myelination 29 .…”
Section: Resultsmentioning
confidence: 99%
“…3e , Supplementary Data 5 ) were the pathways most represented. β1 integrin and RhoC were constituents of these three pathways ( Supplementary Data 5 ), suggesting a potentially important role for RhoC, given that β1 integrin and other small Rho GTPases and effectors (Rac1, Cdc42, Rock and Mlck) are required for axo-glial interactions 6 21 26 27 28 . Similarly, 9 out of the 10 most abundant pathways shared the heterotrimeric G proteins encoded by Gnb1 , Gnb2 , Gnb2L1 , Gnao1 and Gnai2 ( Supplementary Data 5 ), which expand the notion that G-protein signalling is a major contributor of radial sorting and myelination 29 .…”
Section: Resultsmentioning
confidence: 99%
“…MeCbl did not promote the expression of P0 ( Figure 4A ) and MAG ( Figure 4B ) in SCs in neither conditions. In SCs culture, P0 is clearly detectable even in the growth medium and the expression of MAG peaks at 48 h under the differentiation condition ( Leitman et al, 2011 ). We therefore assumed that it might be difficult to detect the increasing expression of the markers in the promyelinating SCs by MeCbl and focused on the markers in the myelinating state.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, in the differentiation medium MeCbl promoted the expression of MBP and Acly ( Figures 4C,D ), whereas it did not affect the expression of P0 and MAG ( Figures 4A,B ). Because the expression of P0 was observed even in the growth medium and the expression of P0, MAG, and MBP reaches the plateau at 36–48 h under the differentiation medium ( Leitman et al, 2011 ; Wu et al, 2011 ), it seemed to be difficult to utilize our experimental method cultured without axons as an estimation of the expression for promyelinating markers such as P0 and MAG and we also presumed that SCs culture without DRG axons for longer period such as 4 or 5 days is not appropriate for an estimation for the MBP expression. MeCbl neither affect SCs under the growth medium (proliferation in Figure 1 ; the Akt activity in Figures 2C,D ; the expression of myelination markers in Figure 4 ) nor promote the expression of MBP at 7 days, earlier stage in the differentiation process, in cocultured DRGs/SCs ( Figures 5A–F ).…”
Section: Discussionmentioning
confidence: 99%
“…Since our data indicate that NMII is a negative regulator of both oligodendrocyte branching and myelin protein expression, it will be important to establish how these processes are coordinated in vivo , and whether other pathways also regulate NMII activity. Of note, recent data from our laboratory has shown that downregulation of myosin light chain kinase (MLCK), an activator of NMII, promotes myelin protein expression in Schwann cells (Leitman et al 2011). Whether MLCK has a similar role in OPC development is currently under study, but we hypothesize that regulation of NMII activity might be a common target for other pathways converging in oligodendrocyte cytoskeletal remodeling and differentiation (Miyamoto et al 2007; Rajasekharan et al 2009).…”
Section: Discussionmentioning
confidence: 99%